The OECD transfer pricing guidelines: an analysis of their application in the South Africa legal regime - Allan, Onsando Omari (Department of Commercial Law, 2026)
The provisions of S 31 of the Income Tax Act 58 of 1962 governing certain cross border transactions amongst entities form the basis of transfer pricing legal regulatory regime in South Africa. The arm's length principle forms the backbone of applying the provisions of the section. The existing legislation is wide in scope hence difficult to apply on the taxpayer's hand; consequently, in some instances it does not serve its intended purpose. For this reason, the South Africa Revenue Service (SARS) has provided a practice note (SARS practice note No. 7 of 1999) which gives guidance on the determination of taxable income of certain persons from international transactions. The practice note is largely based on the Organisation of Economic Cooperation and Development (OECD) comprehensive transfer pricing guidelines. These guidelines are found in the OECD Report, Transfer Pricing Guidelines for Multinational Enterprises and Tax Administrations (1997) These guidelines have increasingly been adopted by many states. South Africa is a non-member state of OECD Model Tax Convention but has however adopted the transfer pricing guidelines therein. This study examines the OECD transfer pricing guidelines, with a view of analysing the manner and extent to which South Africa has adopted them in its current transfer pricing policy. The unique South African economic situation is taken into account. The rationale and extent to which such guidelines have been adopted is relevant and critical in determining efficacy. The findings of this study are threefold. Firstly, the OECD transfer pricing guidelines provide globally accepted standards and methodology by which tax authorities act in common interest to share satisfactorily in the tax which is properly due to them from the taxpayer. Secondly, South Africa has, to a larger extent, managed to keep abreast with the international developments in transfer pricing and compares favourably with the OECD guidelines. Finally, existing legislation has shortcomings such as regulation of financial intra-group assistance services especially the characterisation of certain intra-group debt for transfer purposes. This suggests deviations from the OECD guidelines. Therefore, whether existing law suites local circumstances is doubtable.